2017
DOI: 10.1007/s12253-017-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-27 rs153109 and rs17855750 Polymorphisms with Risk and Response to Therapy in Acute Lymphoblastic Leukemia

Abstract: Interleukin (IL)-27 is a cytokine with important anti-cancer activity. This study has evaluated the effects of IL-27 rs153109 and rs17855750 single nucleotide polymorphisms (SNPs) on risk of acute lymphoblastic leukemia (ALL) development, as well as their impact on prognosis and patient survival. A total of 200 patients and 210 healthy subjects were genotyped by polymerase chain reaction-restriction fragment length polymorphism. We observed a higher frequency of rs153109 AG and rs17855750 TG genotypes and alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…Our previous team work had proved that serum IL-27 level was higher in the PL group than women in the TL group [25]. In the present study, qPCR test ( Fig.…”
Section: Expression Of Il-27rα In Human Fms In Ptli and Tl Groupsupporting
confidence: 57%
“…Our previous team work had proved that serum IL-27 level was higher in the PL group than women in the TL group [25]. In the present study, qPCR test ( Fig.…”
Section: Expression Of Il-27rα In Human Fms In Ptli and Tl Groupsupporting
confidence: 57%
“…Several studies examined the association between DOI:10.31557/APJCP.2020.21.9.2507 IL-27 polymorphisms and the risk of various cancer (Wei et al, 2009;Zhao et al, 2009;Guo et al, 2012;Huang et al, 2012;Pan et al, 2012;Tao et al, 2012;Peng et al, 2013;Munretnam et al, 2014;Tang et al, 2014;Zhang et al, 2014a;Zhang et al, 2014b;Lyu et al, 2015;Pu et al, 2015;Zhang et al, 2015;Zhou et al, 2015;Ge and Xiao, 2016;Wang et al, 2016;Yu et al, 2016;Nie et al, 2017;Ghavami et al, 2018). The findings were controversial, though it is difficult to clarify the inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that IL-27 possesses antitumor activities against a variety of tumor types (Nagai et al, 2010;Di Carlo et al, 2014;Yoshida and Hunter, 2015;Yoshimoto et al, 2015). IL-27 is a polymorphic gene and several studies examined the association between IL-27 gene polymorphisms and risk of various cancers including, non-small-cell lung cancer (NSCLC) (Ge and Xiao, 2016), acute lymphoblastic leukemia (ALL) (Ghavami et al, 2018), nasopharyngeal carcinoma (NPC) (Wei et al, 2009;Pan et al, 2012), colorectal cancer (CRC) (Guo et al, 2012;Huang et al, 2012;Lyu et al, 2015), prostate cancer (PCa) (Munretnam et al, 2014), papillary thyroid carcinoma (PTC) (Zhang et al, 2015;Nie et al, 2017), hepatocellular carcinoma (HCC) (Peng et al, 2013), renal cell carcinoma (RCC) (Pu et al, 2015), osteosarcoma (Tang et al, 2014), esophageal cancer (Tao et al, 2012), cervical cancer (Wang et al, 2016), endometrial cancer (Yu et al, 2016), ovarian cancer (Zhang et al, 2014b), breast cancer (Zhang et al, 2014a), glioma (Zhao et al, 2009), and bladder cancer (Zhou et al, 2015). However, the findings of these studies have been controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In caecal ligation puncture-induced lung in ammation mice model, elevated IL-27 levels were observed in the lung, serum, and bronchoalveolar lavage uids, and IL-27 neutralizing antibody could reduce lung injury and improve survival [12,13]. Our previous team work also demonstrated that IL-27 could induce a proin ammatory response in human fetal membrane, mediating in preterm labor [14]. In regards of the above evidence, we hypothesized that IL-27 could participate in PTLI by regulating neutrophils in ltration at the maternal and fetal interface.…”
Section: Introductionmentioning
confidence: 90%